Program positive parenting sebagai upaya pencegahan risiko stunting - Tambun, Yetty Mariani; Manurung, Suryani; Lestari, Tri Riana; Aprianti , Tutty; Pudentiana, Pudentiana (JOURNAL OF Public Health Concerns, 2024)
Background: Stunting is a condition of failure to thrive as a result of chronic malnutrition, which causes children to grow too short and thin for their age. Currently, stunting is seen as a serious health problem in society, in the world and in Indonesia. The South Jakarta City Government found 640 toddlers suspected of stunting or slow growth and development. Meanwhile, of that number, the Mayor of South Jakarta said that 203 toddlers had been determined to have stunting status. Efforts to handle stunting prevention for those suspected of stunting were 640 and those who had been determined to have stunting were 203 spread across 15 locations in South Jakarta sub-districts, namely determining parenting patterns and foster parents. Purpose: To provide increased ability and skills of health cadres in implementing program positive parentings and improving the abilities of mothers or mothers who have toddlers. Method: Activities are carried out using counseling, demonstration, discussion and participatory action review monitoring evaluation methods Results: Obtaining an agreement on the implementation of a program positive parenting with the local government and the implementation of the socialization of the program positive parenting (P3) to health cadres, the implementation of the program positive parenting (P3) to pregnant women and mothers with toddlers, and the implementation of the nutrition monitoring calendar in the Ragunan Village Health Center, South Jakarta. Conclusion: Community service for the program positive parenting provides an increase in the ability and skills of health cadres in implementing the program positive parenting and improving the ability of mothers with toddlers in applying the nutrition monitoring calendar to detect the risk of stunting. Suggestions: In the future, for cadres who already have the ability, it is hoped that they can periodically monitor the implementation of positive parenting in pregnant women and mothers with toddlers so that they can minimize the risk of stunting. Keywords: Program positive parenting; Pregnant women; Stunting; Toddlers Pendahuluan: Stunting merupakan kondisi gagal tumbuh sebagai dampak kekurangan gizi kronis, yang menyebabkan anak menjadi tumbuh terlalu pendek dan kurus pada usianya. Saat ini, stunting dipandang sebagai masalah kesehatan yang serius di masyarakat, di dunia maupun di Indonesia. Pemerintah Kota Jakarta Selatan menemukan 640 balita terduga stunting atau lambat tumbuh kembang. Sementara itu, dari jumlah tersebut, Wali Kota Jakarta Selatan menyebutkan sebanyak 203 balita yang sudah ditetapkan berstatus stunting. Upaya penanganan pencegahan stunting terhadap yang terduga stunting yakni sebanyak 640 dan yang sudah ditetapkan mengalami stunting sebanyak 203 yang tersebar di 15 lokasi kelurahan Jakarta Selatan yakni menetapkan pola asuh dan orangtua asuh.  Tujuan: Untuk memberikan peningkatan kemampuan dan keterampilan kader kesehatan dalam mengimplementasikan program positive parenting dan meningkatkan kemampuan ibu atau ibu yang memiliki balita. Metode: Kegiatan dilaksanakan dengan menggunakan metode penyuluhan, demonstrasi, diskusi dan evaluasi monitoring kaji tindak partisipastif. Hasil: Mendapatkan kesepakatan pelaksanaan program pengasuhan positive parenting dengan pemerintah daerah dan terlaksananya sosialisasi program positive parenting (P3) pada kader kesehatan, implementasi program positive parenting (P3) kepada ibu hamil dan ibu yang memiliki balita, dan penerapan kalender monitoring gizi di kelurahan Puskesmas Kelurahan Ragunan Jakarta Selatan. Simpulan: Pengabdian masyarakat program positive parenting memberikan peningkatan kemampuan dan keterampilan kader kesehatan dalam mengimplementasikan program positive parenting dan meningkatkan kemampuan ibu yang memiliki balita dalam mengaplikasikan kalender monitoring gizi untuk mendeteksi risiko stunting. Saran: Untuk kedepannya, bagi kader yang sudah memiliki kemampuan, diharapkan dapat secara berkala memantau penerapan positive parenting pada ibu hamil dan ibu yang memiliki balita sehingga dapat meminimalkan risiko terjadinya stunting.